Innovation startups: Study of software applications to optimize home delivery of products. - Medina Muñoz, Jonathan Enrique; Orellana Parra, Marcos Giovanny (Journal of business and entrepreneurial studie, 2023)
This research focuses on a comparative study between the levels of rice exports before and during dollarization, corresponding to the years 1980-2020; thus, the information from the World Bank, Central Bank of Ecuador and SENAE is used as a data base, which eventually leads us to a non-experimental research with a quantitative approach and through the t-test was able to determine the existence of a significant change in rice exports before and during dollarization. On the other hand, the coefficient of determination allows us to appreciate that with dollarization there is a 10% incidence between price and export levels, as well as establishing that during this stage, dependence on international relations and high production costs influence the degree of competitiveness of the price of rice. This research focuses on a comparative study between the levels of rice exports before and during dollarization, corresponding to the years 1980-2020; thus, the information from the World Bank, Central Bank of Ecuador and SENAE is used as a data base, which eventually leads us to a non-experimental research with a quantitative approach and through the t-test was able to determine the existence of a significant change in rice exports before and during dollarization. On the other hand, the coefficient of determination allows us to appreciate that with dollarization there is a 10% incidence between price and export levels, as well as establishing that during this stage, dependence on international relations and high production costs influence the degree of competitiveness of the price of rice.